Evaluating the placement of PIT tags in tropical river fishes: a case study involving two Mekong River species - Grieve, Bettina; Baumgartner, Lee J.; Robinson, Wayne; Silva, Luiz G.M.; Pomorin, Karl; Thorncraft, Garry; Ning, Nathan (Fisheries research, 2018)
•PIT tags can be retained in Striped catfish and Goldfin tinfoil barbs.•Tag retention is not influenced by the location of the tags (chest, gut, shoulder).•Mortality and growth are similarly not influenced by the location of the tags.•PIT tags offer a reliable option for tracking fish in tropical rivers.•Edible species would best be tagged in the region least eaten - i.e. the gut. Fish communities are becoming increasingly threatened in many tropical river-floodplain systems due to the construction of dams and other physical barriers. Efficient tagging techniques are urgently needed to better understand the movement ecology of tropical river-floodplain species — both at a fundamental level and in response to the effects of barriers. Passive Integrated Transponder (PIT) tagging has been successfully used to quantify fish movements in many temperate riverine species, but its effectiveness on tropical riverine species remains largely untested. We investigated the potential use of PIT tags in two tropical species from the Mekong River — Pangasianodon hypophthalmus (Striped catfish) and Hypsibarbus malcolmi (Goldfin tinfoil barbs). Two separate, but concurrent, 50-day experiments were conducted on the two species to determine whether (1) the PIT tags can be retained within the fish, without affecting their mortality or growth, and (2) the outcomes for tag retention, fish mortality, and/or fish growth are influenced by the location of the tags in the fish. Results indicated that, for both species, PIT tags can be retained in the chest, gut or shoulder without affecting mortality or growth. This suggests that PIT tags could be successfully used in a range of body locations in Striped catfish and Goldfin tinfoil barbs in the Mekong River. However, the Mekong fishery is a highly important food source for the people of its neighbouring countries — thus, the most suitable tag location in large-bodied species would be the gut region, as the gut, and tag, are most likely to be removed prior to human consumption.